Copepoda: Developments in Ecology, Biology and Systematics
DOI: 10.1007/0-306-47537-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the study of the life cycles of Antarctic copepods

Abstract: Different approaches to the study of life cycle strategies of Antarctic copepods are described in an attempt to shed new light on our present knowledge. To date, most studies were carried out on abundance, horizontal and vertical distribution and stage composition during different seasons and in various regions. Hence, the seasonal pictures had to be compiled from different years and sampling regions. The physiological method includes measurements on e.g. egg production, feeding, respiration and excretion rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
8

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 75 publications
(87 reference statements)
0
33
0
8
Order By: Relevance
“…Among the Southern Ocean zooplankton, a lot is known about the seasonal vertical migration behaviour of copepods. Most of them migrate seasonally, however, and show distinct species-and stage-specific and regional differences in migration amplitude and timing (Atkinson et al, 1992;Ward et al, 1997;Schnack-Schiel, 2001). Since there were no net hauls of plankton near the moorings during their deployment period, we can only speculate about the species composition of zooplankton whose migration is documented by our measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Among the Southern Ocean zooplankton, a lot is known about the seasonal vertical migration behaviour of copepods. Most of them migrate seasonally, however, and show distinct species-and stage-specific and regional differences in migration amplitude and timing (Atkinson et al, 1992;Ward et al, 1997;Schnack-Schiel, 2001). Since there were no net hauls of plankton near the moorings during their deployment period, we can only speculate about the species composition of zooplankton whose migration is documented by our measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Conover 1988, Conover & Huntley 1991, Atkinson 1998, Schnack-Schiel 2001. Within the same environment, it is widely held that congener species of copepods have unique assortments of life-history traits, limiting interactions among them.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that copepods use protein as a metabolic substrate during overwintering in order to preserve lipid stores for reproduction (Kirkesaeter 1977, Jónasdóttir 1999, Schnack-Schiel 2001. It has also been suggested that protein may be used to fuel egg release in Neocalanus plumchrus (Evanson et al 2000).…”
Section: Protein Contentsmentioning
confidence: 99%
“…Evidence for protein use during overwintering includes observed declines in total protein content (Kirkesaeter 1977); declines in nitrogen content (Tande 1982, Ohman et al 1989; low but measurable rates of ammonium excretion (Conover & Corner 1968, Cowen 1982; and low O:N ratios (Conover & Corner 1968, Kosobokova 1990, Schnack-Schiel 2001. Calanoid copepods are primarily ammonotelic, whereby the catabolism of proteins and nucleic acids produces ammonium (Corner & Cowey 1968).…”
Section: Abstract: Copepod Overwintering · Lipid Physiology · Proteimentioning
confidence: 99%